Relationship between corporate social responsibility and organizational resilience: conceptual framework - Ramakrishnan, Suresh; Ru, Duan (International Journal of Psychosocial Rehabilitation, 2020)
Organizational resilience is the capacity to survive and develop through the turbulent environmental changes. It is crucial to firms’ sustainable development. The paper reviews literature on definition, conceptualization, antecedents of organizational resilience and operationalize it with three aspects: long-term financial performance, financial volatility and financial performance decline and recovery during unexpected shocks. The former two aspects are concerned with the accumulation of firms’ economic strength and risk management ability. Both of them are closed connected with formation of organizational resilience and prepare firms with capability to cope with unanticipated shocks, whereas the latter aspect is demonstration of organizational resilience. Based on the operationalization, the paper establishes relationship between CSR and organizational resilience to explore whether and by which mechanism that CSR practice affects organizational resilience development. The paper integrates two streams of research on CSR’s effect on financial performance and financial risk under the framework of organizational resilience. Furthermore, it contributes to literature on the antecedents of organizational resilience.